Legal Ableism, Interrupted: Developing Tort Law & Policy Alternatives to Wrongful Birth & Wrongful Life Claims - Lydia X. Z. Brown (Disability Studies Quarterly, 2018)
Early in 2016, the widely acclaimed film Me Before You premiered nationally to a spate of disabled-led protests against the ableism in the film's core story – that of a wealthy, physically disabled young man whose romantic and sexual relationship with a young woman hired as his caregiver (and quasi-maternal or mentoring figure) leads to his choice to kill himself to avoid living further while disabled, and to bequeath his assets to her. Protested as a "disability snuff film" by leading groups like Not Dead Yet, disabled activists lambasted the film for its glorification of assisted suicide as a brave and heroic choice because of the protagonist's disability – criticizing the writers for sending a very strong message that it is better to be dead than to live as disabled, however that might be defined or understood. U.S. law has often embodied that very same message despite the existence of civil rights protections for people with disabilities, and most particularly and glaringly in its adoption of wrongful birth and wrongful life claims as cognizable in tort. In this paper, I aim to provide brief context on the nature and history of wrongful birth and wrongful life claims, examine the myriad social harms toward disabled people that stem from their assertion, explore non-ableist purposes for which these claims might be brought, and propose potential legal and policy mechanisms as alternative means for achieving their possible legitimate purposes without reliance on them.
Keywords: wrongful birth; wrongful life; legal discourse; ableism; agency; reproductive justice; bioethics; prenatal diagnosis; tort law; social services